Heterogeneity of Radial Glia-Like Cells in the Adult Hippocampus. (4th January 2016) - Gebara, Elias; Bonaguidi, Michael Anthony; Beckervordersandforth, Ruth; Sultan, Sébastien; Udry, Florian; Gijs, Pieter-Jan; Lie, Dieter Chichung; Ming, Guo-Li; Song, Hongjun; Toni, Nicolas
Abstract: Adult neurogenesis is tightly regulated by the neurogenic niche. Cellular contacts between niche cells and neural stem cells are hypothesized to regulate stem cell proliferation or lineage choice. However, the structure of adult neural stem cells and the contact they form with niche cells are poorly described. Here, we characterized the morphology of radial glia-like (RGL) cells, their molecular identity, proliferative activity, and fate determination in the adult mouse hippocampus. We found the coexistence of two morphotypes of cells with prototypical morphological characteristics of RGL stem cells: Type α cells, which represented 76% of all RGL cells, displayed a long primary process modestly branching into the molecular layer and type β cells, which represented 24% of all RGL cells, with a shorter radial process highly branching into the outer granule cell layer-inner molecular layer border. Stem cell markers were expressed in type α cells and coexpressed with astrocytic markers in type β cells. Consistently, in vivo lineage tracing indicated that type α cells can give rise to neurons, astrocytes, and type β cells, whereas type β cells do not proliferate. Our results reveal that the adult subgranular zone of the dentate gyrus harbors two functionally different RGL cells, which can be distinguished by simple morphological criteria, supporting a morphofunctional role of their thin cellular processes. Type β cells may represent an intermediate state in the transformation of type α, RGL stem cells, into astrocytes. Abstract : Model of the lineage relationship of type α and type β cells in the adult mouse hippocampus under basal conditions. Type α cells can self-renew (1) and also generate type 2 neural progenitors (2), type β cells (3) and astrocytes (4). Type β cells do not divide, but may revert to type α cell (??) or transform into astrocytes (5). Also shown are marker expression.